Mixed Metal Complexes of Succinic Acid: The Effect of pH and Ionic Speciation Modeling - Eissa Mohamed Almbrok; Hassana Abdelkader; Adda Mohamed (المجلة الأفروآسيوية للبحث العلمي, 2025)
The potentiometric behavior of succinic acid (H₂Succ) and its complexation with copper(II) and zinc(II) ions were systematically investigated to elucidate the influence of pH and ionic speciation in single and mixed-metal systems. Titrations were performed at 25 °C in 0.1 M KCl to determine the acid dissociation and complex formation constants. The dissociation constants of the free ligand were found to be pKa₁ = 4.6 and pKa₂ = 5.2. In the presence of Cu²⁺ and Zn²⁺ ions, significant shifts in the potentiometric curves confirmed the formation of stable complexes, with stability constants log β = 6.3 for Cu²⁺–Succ and log β = 4.9 for Zn²⁺–Succ systems. The mixed Cu²⁺ + Zn²⁺ system exhibited synergistic stabilization with an overall log β = 11.4, suggesting the formation of binuclear or bridging mixed-metal complexes. Ionic speciation modeling demonstrated that the predominant species distribution depends strongly on pH, with Cu-containing complexes dominating in mildly acidic to neutral conditions. These findings highlight the cooperative interactions between Cu²⁺ and Zn²⁺ in mixed systems and provide insight into the coordination chemistry of dicarboxylic acids under varying protonation equilibria.